The Effect of Public and Private Decisions on University Governance on the Transnational Relations of American-Associated Universities in the Middle East - Rasmus Bertelsen (Revue des Mondes Musulmans et de la Méditerranée)
This paper analyzes the effect of public and private decisions on university governance on how historic and current American-associated universities in the Middle East have and continue to connect as transnational actors with a multitude of public, private and civil society actors in American society. These universities are the classic missionary universities in Beirut and Cairo (the American University of Beirut, Lebanese American University and the American University in Cairo) as well as the many branch campuses and new universities with American accreditation or partnership which have appeared especially in the Gulf States. The ability of these universities to engage with actors in American society and the Middle Eastern host society is explained by their model of governance highlighting public and private decisions on primarily owner-ship structure and non- or for-profit status. Affiliated, non-profit status explains academic reputation, while proprietary, for-profit status is detrimental. Academic reputation is the basis of the relationships these universities maintain with American private, public and civil society actors.